Registered Replication Report on Mazar, Amir, and Ariely (2008). Issue 3 (September 2018) - Verschuere, Bruno; Meijer, Ewout H.; Jim, Ariane; Hoogesteyn, Katherine; Orthey, Robin; McCarthy, Randy J.; Skowronski, John J.; Acar, Oguz A.; Aczel, Balazs; Bakos, Bence E.; Barbosa, Fernando; Baskin, Ernest; et al.
The self-concept maintenance theory holds that many people will cheat in order to maximize self-profit, but only to the extent that they can do so while maintaining a positive self-concept. Mazar, Amir, and Ariely (2008, Experiment 1) gave participants an opportunity and incentive to cheat on a problem-solving task. Prior to that task, participants either recalled the Ten Commandments (a moral reminder) or recalled 10 books they had read in high school (a neutral task). Results were consistent with the self-concept maintenance theory. When given the opportunity to cheat, participants given the moral-reminder priming task reported solving 1.45 fewer matrices than did those given a neutral prime (Cohen's d = 0.48); moral reminders reduced cheating. Mazar et al.'s article is among the most cited in deception research, but their Experiment 1 has not been replicated directly. This Registered Replication Report describes the aggregated result of 25 direct replications (total N = 5, 786), all of which followed the same preregistered protocol. In the primary meta-analysis (19 replications, total n = 4, 674), participants who were given an opportunity to cheat reported solving 0.11 more matrices if they were given a moral reminder than if they were given a neutral reminder (95% confidence interval = [−0.09, 0.31]). This small effect was numerically in the opposite direction of the effect observed in the original study (Cohen's d = −0.04).